Distribution of Sipuncula in relation to the Environmental Characteristics at Selected Sites in Kuching Division, Sarawak - Nurnadirah, binti Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study focus on soft substrate. Rectangular plot (20, 000 m2) was made parallel to the beach. The distribution of peanut worm were based on burrows counting and actual extraction. The distance between burrows and distance of burrows from high tide and low tide water marks were recorded. Simultaneously, pH, salinity and temperature of pore water were recorded while sediments cores were taken for sediment moisture and particle size analysis. Burrowing behaviour in the laboratory was carried out using life specimen. The size of peanut worm also were recorded. Only Sipunculus nudus were found in this study and the highest density of adult was at Kg Pugu with 270 burrows per 20, 000 m2 while the highest juvenile density was found at Trombol with172 individuals per 15 m2. They were found along in middle watermarks along intertidal area. It was observed that sipunculans inhabit habitat which has these characteristics: (i) pH: 6.72 - 7.28 (ii) salinity: 29.44 - 35.6 PSU (iii) percentage of sediment moisture: 72.11 -79.80 % (iv) fraction of sediment: sand. Six patterns of burrow show were observed on the surface of sediment. Size of adult S. nudus ranged from 15.8 -30.0 cm and their burrow range from 47 - 64 cm while the size of juvenile S. nudus were about 4.0- 5.0 cm and they were found just few cm beneath the sediment. The burrowing ability of the juvenile depending on the water level covering the sediment. The time for burrowing was about 31 s until 507 s.